Computer Aided Verification of Lamport’s Fast Mutual Exclusion Algorithm - Using Coloured Petri Nets and Occurrence Graphs with Symmetries - Jørgensen, Jens Bæk; Kristensen, Lars Michael (DAIMI Report Series, 1997)
In this paper, we present a new computer tool for verification of distributed systems. As an example, we establish the correctness of Lamport’s Fast Mutual Exclusion Algorithm. The tool implements the method of occurrence graphs with symmetries (OS-graphs) for Coloured Petri Nets(CP-nets). The basic idea in the approach is to exploit the symmetries inherent in many distributed systems to construct a condensed state space. We demonstrate a signigicant increase in the number of states which can be analysed. The paper is to a large extent self-contained and does not assume any prior knowledge of CP-nets (or any other kinds of Petri Nets) or OS-graphs. CP-nets and OS-graphs are not our invention. Our contribution is development of the tool and verification of the example. Index Terms: Modelling and Analysis of Distributed Systems, Formal Verification, Coloured Petri Nets, High-Level Petri Nets, Occurrence Graphs, State Spaces, Symmetries, Mutual Exclusion.